Barriers to the management of children under five exposed to HIV in the rural areas of South Africa - Sibusiso F. Buthelezi; Regis R.M. Modeste; Deliwe R. Phetlhu (AOSIS, 2021)
Background: South Africa has made enormous progress in reducing mother-to-child transmission (MTCT) of human immunodeficiency virus (HIV), however, MTCT and AIDS related death persist among children particularly in the rural areas. Lack of adherence to health policies and guidelines implementation remain one of the contributory factors to poor management of HIV-exposed children. Hence, the need to deeply explore the complexity of the problems and understand the barriers to the management of HIV exposed children in the rural areas. Objectives: To explore and synthesise the barriers to the management of children under 5 years old exposed to HIV in rural areas in South Africa. Method: An integrative literature review was conducted. An electronic search was conducted on several databases. The researchers applied the Boolean ' AND'/'OR' in combination with phrases such as 'HIV infection*', 'HIV transmission', 'HIV-exposed infant*, child*, and neonate*' and 'South Africa*'. Included studies were limited to South Africa, and articles were written in English and published in peer-reviewed journals from 2005 to 2018. Both qualitative and quantitative studies between 2005 and 2018 were utilised. Results: The findings highlighted that healthcare institution-related barriers, healthcare provider-related barriers, patient-related barriers and Socio-economic-related barriers were the significant barriers to the management of HIV-exposed children in the rural areas. Conclusion: Continuous engagement with all relevant stakeholders should remain a priority in protecting HIV-exposed children. It is evident that there exist gaps in the current implementation of prevention of mother-to-child transmission (PMTCT), especially in rural areas. Therefore, intervention strategies that could improve implementation of PMTCT policy guidelines for HIV-exposed children in rural areas are needed.